TRAUMATIC VENTRICULITIS IN AN AFRICAN OSTRICH: A CASE REPORT - Adam, Mohammed; Ajadi, Abdullateef Abiodun; Atata, Jamila Abiodun; Akanbi, Olatunde Babatunde (Media Kedokteran Hewan, 2022)
Traumatic ventriculitis or hardware disease is the gizzard perforation by sharp foreign bodies (metallic or sharp object) that leads to ulcerative lesions.The present Case Report was to investigate through post mortem examination the cause of African ostrich death. Necropsy was conducted on a dead male adult African Ostrich presented to the postmortem unit of the Department of Veterinary Pathology, University of Ilorin, Ilorin, Nigeria. The gross lesions showed multifocal ecchymotic and petechial haemorrhages and lacerations on the left shank and thigh as well as the cloaca and vent of the bird. A perforation of the proventriculus with adhesion of a pointed nail-like metallic sharp object of 9.4 cm in length was observed. Histopathological findings revealed obliteration of tubular and vascular congestion which predisposed the animal to metabolic disorder.